Modification of ilmenite surface properties by superficial dissolution method. (June 2016) - Parapari, Parisa Semsari; Irannajad, Mehdi; Mehdilo, Akbar
Graphical abstract: Highlights: Acid surface dissolution converts some Fe 2+ to Fe 3+ ions on ilmenite surface. Surface dissolution results in the formation of an insoluble hydrophobic layer of Fe(Ol)3 . Acid surface dissolution decreases the IEP of ilmenite and improves its floatability. Abstract: Acid surface dissolution as a pretreatment method converts Fe 2+ ions on the ilmenite surface to Fe 3+ ions. XPS analysis showed that the content of Fe 3+ increases from 48.5% to 59.8% after surface dissolution for 15 min in a solution of sulfuric acid with a concentration of 10%. This conversion, without any phase transformation, decreases the zeta potential of ilmenite in a wide pH range, resulting in a shift in IEP (Iso-Electric Point) from a pH of 5.4 to 2.3. FTIR spectra and zeta potential measurements showed that the increase of oleate ions adsorption on the ilmenite surface, resulting from the surface dissolution process, is insignificant. After surface dissolution, the formation of more ferric iron oleate species (Ksp = 10 −29.7 ) being more stable than ferrous iron oleate (Ksp = 10 −15.5 ) compounds yields an increase of ilmenite hydrophobicity and floatability in a wide pH range. Using 3.65 × 10 −4  M sodium oleate at a pH of 6.3, the maximum flotation recoveries are obtained as 73.5% and 92% for non-treated and acid pretreated ilmenite, respectively.